2003
DOI: 10.1034/j.1399-6576.2003.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal midazolam added to bupivacaine improves the duration and quality of spinal anaesthesia

Abstract: The addition of intrathecal midazolam to bupivacaine significantly improves the duration and quality of spinal anaesthesia and provides prolonged perioperative analgesia without significant side-effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
58
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 24 publications
13
58
1
2
Order By: Relevance
“…When intrathecal midazolam is used, all patients should be closely monitored intra-and postoperatively. The findings of this study are consistent with those of earlier reported studies by Bharti et al 13 and Batra et al 14 , who found that the duration of sensory blockade was significantly prolonged after the addition of midazolam to intrathecal bupivacaine. The addition of intrathecal midazolam did not significantly alter the peak level of sensory blockade that was achieved after the onset of spinal anaesthesia.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…When intrathecal midazolam is used, all patients should be closely monitored intra-and postoperatively. The findings of this study are consistent with those of earlier reported studies by Bharti et al 13 and Batra et al 14 , who found that the duration of sensory blockade was significantly prolonged after the addition of midazolam to intrathecal bupivacaine. The addition of intrathecal midazolam did not significantly alter the peak level of sensory blockade that was achieved after the onset of spinal anaesthesia.…”
Section: Discussionsupporting
confidence: 83%
“…Many earlier studies did not find an increased duration of motor blockade after the addition of midazolam to intrathecal bupivacaine 10,11,14,16 .Further studies on larger samples are needed to evaluate and confirm this finding. The present study is consistent with other studies conducted by Goodchild et al 9 and Batra et al 14 , who found no added haemodynamic changes, such as hypotension and bradycardia, or shivering, respiratory depression, desaturation, pruritus, urinary retention, nausea or vomiting from the baseline when intrathecal midazolam was added to intrathecal bupivacaine 10,13,14,17,18 . The addition of 1 mg midazolam to intrathecal bupivacaine causes no significant haemodynamic disturbances, and is relatively free from common side-effects.…”
Section: Discussionsupporting
confidence: 82%
“…Others also observed that intrathecal midazolam produced significant postoperative pain relief in patients undergoing lower abdominal and perineal surgeries. 12,13,15,17 Midazolam produces spinally mediated analgesia that is different in quality from that produced by the μ-opioid agonist fentanyl. The analgesic effects of intrathecal midazolam have been proposed to be due to its intrathecal spinal receptor interactions affecting the type A gamma-aminobutyric acid receptors.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] Previous reports have shown that administration of intrathecal midazolam with local anesthetics prolongs the duration of spinal anesthesia and produces longer postoperative analgesia after lower abdominal and perianal surgeries. [11][12][13][14][15][16][17] None of these studies reported any serious adverse effects in patients receiving intrathecal midazolam. A large cohort study investigating the adverse neurological effects of intrathecal midazolam has also found no association between intrathecal midazolam and neurologic symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The duration of sensory block in our study was in resemblance to that of TM Krishna et al (2008) who also noticed significant prolongation of sensory block in midazolam-ketaminebupivacaine group as compared to ketaminebupivacaine group. Kathirvel et al (2000) in their study showed that no significant difference occur in duration of sensory block with addition of ketamine to bupivacaine while Bharti N et al (2003) and Mia JY et al (2007) in their study showed that significant prolongation in duration of sensory block occur with addition of midazolam to bupivacaine. Reason for short duration of sensory block in Group K may be due to shorter duration action of ketamine as compared to bupivacaine.…”
Section: Observations and Results Table 1: Demographic Datamentioning
confidence: 99%